Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan Pada PT Hanjaya Mandala Sampoerna Tbk Tahun 2018 - 2023 - Khoharudin, Ali; Solikah, Mar’atus; Puspita, Erna (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Performance is a measure or assessment of the extent to which a company can achieve the desired goals and results. One way to assess the financial performance of a company is to carry out financial report analysis. This research aims to determine financial performance using financial ratios at PT. Hanjaya Mandala Sampoerna Tbk which occurred before the disaster that hit the world, namely the Covid 19 pandemic, during the Covid 19 pandemic and after the Covid 19 pandemic. This research uses quantitative descriptive methods with analysis techniques using liquidity, solvency, activity and profitability ratios. The information and data for this research come from the annual financial report on the official website of PT. Hanjaya Mandala Sampoerna Tbk. The results of this research are measurements of liquidity, solvency, activity and profitability ratios at PT. Hanjaya Mandala Sampoerna Tbk from 2018 to 2023 which obtained an average performance score with conditions tending to be unhealthy.